Haunting Body, Hideous Beauty: Genre and Representation of Queer Gothic in Hor Taew Tak Trilogy - Mahasupap, Saran (Journal of Letters, 2016)
In Thai contemporary society, gothic film has prosperously gained popularity in Thai film sphere. The dark light of the gothic genre literally delineates dark, danger and intimidation. This genteel label of gothic is unavoidably altered when appropriated to a different cultural platform. In the Thai cinematic, the sense of intimidation and darkness have been shaken from its provenance and combined to concoct an alternative and hybrid form of gothic. The nexus of fear and fun intermingled in this genre can be presented as “global gothic” in which normative gothic is globalized and localized simultaneously. In the meantime, in the films, the Hor Taew Tak trilogy, transgendered people, known as katoey, are portrayed in the film and perfectly fit with their strong stereotypical characteristics of being funny and hilarious. These stereotypes seem to be underlined in the public space through films and soap opera. Interestingly, in the cinematic sphere, Thai films opt for representing transgender people with the implication of being monsters. Even though the sense of comedy and fun is accentuated, there is a certain portrayal of their bodies as being distorted and dehumanized and they are rendered to be queer monsters. This research aims to analyze the Thai films, the Hor Taew Tak trilogy, as the epitomé of the characteristic of “global gothic” in the Thai film industry. In addition, it also investigates and reveals the representation of queer characters and how this is exploited in the stereotypical image of “katoeys” imposed by the mainstream society. เรือนร่างและความงามอันน่าสยดสยองเหลือทน: ประเภทและภาพแทนของเควียร์ในภาพยนตร์ไตรภาคเรื่อง หอแต๋วแตก ศรัณย์ มหาสุภาพ นักวิจัยอิสระ ภาพยนตร์โกธิค (gothic) ได้รับความนิยมอย่างมากในแวดวงภาพยนตร์ของสังคมไทยร่วมสมัย เนื่องจากมักนำเสนอเรื่องราวเกี่ยวกับความมืดมน ภัยอันตราย และความน่าหวาดกลัว ซึ่งเอกลักษณ์ของภาพยนตร์โกธิคจะถูกปรับเปลี่ยนให้เหมาะสมกับพื้นถิ่นของแต่ละวัฒนธรรมอย่างมิอาจหลีกเลี่ยงได้ ทั้งนี้ วงการภาพยนตร์โกธิคไทยนั้นนำความน่าหวาดกลัวและความมืดมัวที่ได้รับอิทธิพลจากต้นกำเนิดของภาพยนตร์โกธิคในประเทศตะวันตกมาประกอบให้กลายเป็นภาพยนตร์สยองแนวใหม่ โดยผสมผสานความน่าหวาดกลัวและความตลกซึ่งเป็นหัวใจหลักของภาพยนตร์แนวนี้เข้าด้วยกัน อาจเรียกได้ว่าเป็นลักษณะร่วมสมัยที่ยังคงมีทั้งกลิ่นอายของวัฒนธรรมโลกและวัฒนธรรมพื้นถิ่นในเวลาเดียวกัน (global gothic) นอกจากนี้ ภาพยนตร์ ไตรภาค หอแต๋วแตก ยังสร้างภาพแทนของตัวละครข้ามเพศหรือกระเทยในภาพยนตร์เรื่องนี้ให้มีลักษณะแบบเดียวกัน คือ ตลกและน่าขบขัน ซึ่งลักษณะนี้ถูกเน้นย้ำในพื้นที่สาธารณะผ่านสื่อภาพยนตร์หรือละคร อย่างไรก็ตาม ภาพยนตร์ไทยมีความน่าสนใจที่มักเลือกนำเสนอตัวละครข้ามเพศด้วยนัยยะของตัวประหลาด ถึงแม้อารมณ์ขันและความตลกจะถูกขับเน้นให้โดดเด่น แต่ยังคงมีการแสดงให้เห็นเรือนร่างที่ผิดเพี้ยน ไม่เหมือนมนุษย์ และเป็นเควียร์ตัวประหลาด บทวิจัยนี้มุ่งวิเคราะห์ภาพยนตร์ไทยไตรภาค หอแต๋วแตก ในฐานะตัวอย่างของ “ลักษณะร่วมสมัยที่ยังคงมีทั้งกลิ่นอายของวัฒนธรรมโลกและวัฒนธรรมพื้นถิ่นในเวลาเดียวกัน” ในอุตสาหกรรมภาพยนตร์ไทย นอกจากนี้ยังศึกษาอภิปรายวิธีการนำเสนอตัวละครเควียร์และการใช้ประโยชน์จากภาพลักษณ์แบบเดียวกันของกระเทยที่ถูกกำหนดโดยสังคมกระแสหลัก